POLLEN CONCENTRATION OF INVASIVE TREE OF HEAVEN (AILANTHUS ALTISSIMA) ON THE NORTHERN GREAT PLAIN, HUNGARY - Vojnich, Viktor; UDVARDY, Orsolya; KAJTOR-APATINI, Dóra; FERENCZ, Árpád; SZARVAS, Adrienn; MAKRA, László; MAGYAR, Donát (Acta herbologica, 2022)
In areas where the tree of heaven (Ailanthus altissima) appears and multiplies, the original vegetation degrades and transforms. The invasive tree of heaven is also of great importance in urban environments, where it causes building damage, static problems and endangers utilities. Ailanthus pollen concentration was measured during the 3-year period 2016-2018 at three county capitals (Szolnok, Debrecen, Nyíregyháza) of the Northern Great Plain, Hungary (Jász-Nagykun-Szolnok county, Hajdú-Bihar county and Szabolcs-Szatmár-Bereg county), with a 7-day Hirst-type (Burkard) pollen trap. The extent of the prevalence of A. altissima can be deduced from its pollen concentration. For this purpose, multi-year pollen data are displayed on a result map in which areas characterized by different pollen concentrations are represented by colour codes. The mass appearance of A. altissima is a serious problem in almost all areas (national parks, forests, inner city zones and towns), where its control/eradication would cost millions of euros. Pollen monitoring provides information on the size of A. altissima stands and provide a basis for proposals and plans for measures to control this invasive tree species and mitigate the damage caused by it.